Conversion of once‐daily extended‐release tacrolimus is safe in stable liver transplant recipients: A randomized prospective study. Issue 2 (February 2016) - Kim, Jong Man; Kwon, Choon Hyuck David; Joh, Jae‐Won; Sinn, Dong Hyun; Lee, Sanghoon; Choi, Gyu‐Seong; Lee, Suk‐Koo
Abstract : Simplifying the therapeutic regimen of liver transplantation (LT) recipients may help prevent acute rejection and graft failure. The present study aimed to evaluate the efficacy and safety of conversion from twice‐daily tacrolimus to once‐daily extended‐release tacrolimus under concurrent mycophenolate mofetil therapy in stable LT recipients. This randomized, prospective, controlled study included 91 patients who underwent LTs with at least 1 year of posttransplant follow‐up. Conversion was made on a 1 mg to 1 mg basis. No incidences of biopsy‐proven acute rejection, graft failure, or death were reported in either group at 24 weeks. Median serum tacrolimus level of the study group was 20% less than that of the control group at 8 weeks. However, no significant differences regarding biochemical indicators of liver function or serum creatinine levels were observed between the 2 groups. Adverse event (AE) profiles were similar for both groups, with comparable incidences of AEs and serious AEs. No significant differences regarding efficacy or safety were observed between the once‐daily tacrolimus and twice‐daily tacrolimus groups of stable LT recipients. In conclusion, our study suggests that tacrolimus can be safely converted from a twice‐daily regimen to a once‐daily regimen in stable LT recipients. Liver Transpl 22:209–216, 2016, 2015 . © 2015 AASLD.